2019
DOI: 10.1109/access.2019.2923743
|View full text |Cite
|
Sign up to set email alerts
|

Joint Activity Recognition and Indoor Localization With WiFi Fingerprints

Abstract: Recent years have witnessed the rapid development in the research topic of WiFi sensing that automatically senses human with commercial WiFi devices. Past work falls into two major categories, i.e., activity recognition and the indoor localization. The former work utilizes WiFi devices to recognize human daily activities such as smoking, walking, and dancing. The latter one, indoor localization, can be used for indoor navigation, location-based services, and through-wall surveillance. The key rationale behind … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 45 publications
0
100
0
Order By: Relevance
“…With success of mmWave FMCW signals for human sensing, commercial WiFi signals, especially CSI measurements from commercial 802.11n chipsets at low frequency (2.4 GHz) bands, were trained via supervised learning or cross-modal deep learning for human sensing tasks such as device-free localization, activity recognition, fall detection, personal identification, emotion sensing, and skeleton tracking [52]- [62]. Most recently, [60] used annotations from camera images to train fine-grained CSI measurements over 30 subcarriers and 5 frames from 3 transmitting and 3 receiving antennas. The cross-modal deep learning approach showed the great potential of commercial WiFi signals for sensing applications.…”
Section: ) Human Sensingmentioning
confidence: 99%
“…With success of mmWave FMCW signals for human sensing, commercial WiFi signals, especially CSI measurements from commercial 802.11n chipsets at low frequency (2.4 GHz) bands, were trained via supervised learning or cross-modal deep learning for human sensing tasks such as device-free localization, activity recognition, fall detection, personal identification, emotion sensing, and skeleton tracking [52]- [62]. Most recently, [60] used annotations from camera images to train fine-grained CSI measurements over 30 subcarriers and 5 frames from 3 transmitting and 3 receiving antennas. The cross-modal deep learning approach showed the great potential of commercial WiFi signals for sensing applications.…”
Section: ) Human Sensingmentioning
confidence: 99%
“…Accuracy is reported to be high (90% and up) when using CSI and excluding RSSI. Wang et al [16] applied a residual neural network (ResNet [5]) consisting of multiple ResNet layers to a dual-task CNN for both activity recognition and indoor localization for 6 activities at 16 indoor locations. An accuracy was reported of 88% and 95% was reported for activity recognition and indoor localization, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, research often looks into applying remote sensing in this field. It has been shown that indoor localization [6,16,18], measuring physiological signals [11,13,17,20], human identification [2,12], and general human activity recognition/gesture detection [1,7,21,22] are achievable by using CSI. The performances of such systems is comparable to the existing wearable wireless sensor systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with RSSI, CSI has a certain multipath resolution and can sense weak fluctuations of signals on the propagation path. CSI also has a higher sensitivity, a wider sensing range, and stronger sensing reliability [7][8][9][10]. Of course, CSI can also be used in more fine-grained detection, such as gesture recognition using CSI and sleep monitoring using CSI [11,12].…”
Section: Introductionmentioning
confidence: 99%